GEOARCHAEOLOGICAL STUDIES IN URBAN AND SUBURBAN AREAS OF THE ARGOLIS PREFECTURE. - Zananiri, I.; Chiotis, E.; Tsombos, P.; Hademenos, V.; Zervakou, A. (Bulletin of the Geological Society of Greece, 2010)
The application of earth science principles and techniques to the understanding of the archaeo-logical record has become a common practice, while reducing the archaeological risk is possible by clarifying areas of archaeological potential at an early stage. Towards this scope non-invasive geophysical magnetometry surveys were carried out at the city of Argos, successfully locating areas of interest for future excavations. Geoarchaeology studies in the Argolis Prefecture also involved the spatial location of the archaeological protection zones in the city of Nafplio, by combining data from the Official Government Gazettes, aerial photographs and high-resolution satellite images. Another study dealt with the palaeogeographic evolution of the broader Palea Epidavros area; fieldwork comprised electric resistivity soundings, total field magnetic measurements and two research boreholes at different altitudes. Finally, geoarchaeological research was employed to locate rocks suitable for the restoration of the Grave Circle A of Mycenae. The data management and cartographic representation was performed, in all cases, using Geographic Information Systems, where a geographic database was created, including all available information: local geology, topographic features, satellite images and archaeological data.